ANALILIS HUKUM PENGALIHAN OBJEK JAMINAN FIDUSIA KEPADA MASYARAKAT PENERIMA DANA CORPORATE SOCIAL RESPONSIBILITY (CSR) - Ramadhan, Muhammad Syahri (Solusi, 2018)
Research Objective: to analyze the Law of Transfer of Fiduciary Assurance Objects to the Community of Corporate Social Responsibility (CSR) Grantees. Research methods; using the normative juridical method. Result of research: CSR is obligation of company. In order to be free from legal sanctions caused by not issuing CSR funds, the company is required to issue CSR funds even though business activities and financial condition of the company is still not running optimally and the debt agreement of the company is still not settled properly. Therefore, it does not close the possibility of companies providing CSR funds to the public in the form of goods or usually motor vehicles, which where the vehicle should be a fiduciary guarantee object. This of course will lead to legal disputes in front of it between companies as fiduciary givers, creditor as fiduciary receiver and CSR fund recipient community. Company as fiduciary giver if still doing policy of giving of motor vehicle as object of fiduciary guarantee to society of recipient of CSR fund. Then it will cause its own losses for the company because the company as a fiduciary guarantee provider may be subject to .. Article 36 of undang –undang NO.42 Tahun 1999 on Jaminan Fidusia